A comparative prospective study of handsewn versus stapled anastomosis in lower gastrointestinal surgeries - Narayan Prasad Belbase; Aditya Jalan; Bhupendra Nath Patowary; Sujit Kumar (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Though abdominal surgery has been practiced for many centuries, the optimal technique for anastomosis of small bowel and large bowel remains controversial. This study was conducted with objective to compare the outcome of stapled and handsewn technique of anastomosis of the lower gastrointestinal tract. Materials & Methods: This prospective study was done in the Department of General Surgery and Surgical Gastroenterology, College of Medical Sciences, Bharatpur in the period between 1st October 2014 to 30th September 2015. A total of 50 patients who underwent resection and anastomosis for various conditions of small bowel and large bowel were alternatively placed in handsewn and stapled group. Both the groups were compared in terms of mean time required to perform the intestinal anastomosis, mean operating time, postoperative complications like anastomotic leak rate and wound infection rate, and the time of postoperative hospital stay. Results: The mean duration to perform the intestinal anastomosis was 32.04±4.51 minutes in the handsewn group and 11.00±1.91 minutes in the stapled group(p<0.001).The mean operative time was 147.12±20.91 minutes in the handsewn group versus 132.52 ± 15.71 minutes in the stapled group(p<0.05). The mean duration of postoperative hospital stay was 9.04±2.77 days in the handsewn group versus 8.44 ± 2.32 days in the stapled group (p>0.05). There was no significant difference in the anastomotic leak rate and surgical site infection rate among the two groups. Conclusion: Stapling technique can significantly reduce the time for the anastomotic procedure and also the duration of the operation. However, there was no difference in the rate of anastomotic leak and wound infection between the handsewn and stapled anastomosis. Therefore, stapled anastomosis can be considered a better option over handsewn bowel anastomosis.